The invention of modern Italian literature : strategies of creative imagination - Tellini, Gino, 1946- (Toronto Italian studies., 2007)
As an investigation of new expressive processes and stylistic experiences, The Invention of Modern Italian Literature situates prominent Italian writers within the context of modern literature.